2022
DOI: 10.1177/23197145221121084
|View full text |Cite
|
Sign up to set email alerts
|

Back from the Future: Mediation and Prediction of Events Uncertainty through Event-Driven Models (EDMs)

Abstract: The event-driven model (EDM) is an emerging concept in human behavioural research, and understanding how EDMs can promote theory development remains a fundamental quest of predictive science. Traditionally, researchers have heavily depended upon theory confirmation and the inclusion of mediating constructs to clarify uncertainty associated with plausible events (e.g. political, socio-economic, technological, environmental). Though this approach has pushed the field forward, it has also steered mediation resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 77 publications
1
7
0
Order By: Relevance
“…We found that the GI ( product and process) mediates the relationship significantly and positively between GMO (SGMO and IGMO) and OP, but in the case of TGMO, even though the relationship was significant and positive but somewhat weak as compared to SGMO and IGMO. Although it supports the assertion we made (at a significant level), but we further investigated and found there was no indirect v 2 effect (Ogbeibu & Gaskin, 2022;, and based on that, we validate that the GI does not mediate the relationship between TGMO and organization performance. So, our observation comprehends that the functional effect of TGMO has a direct bearing on OP (Papadas et al, 2019) instead of an indirect effect through GI.…”
Section: Moderation Effect Of Svsupporting
confidence: 85%
“…We found that the GI ( product and process) mediates the relationship significantly and positively between GMO (SGMO and IGMO) and OP, but in the case of TGMO, even though the relationship was significant and positive but somewhat weak as compared to SGMO and IGMO. Although it supports the assertion we made (at a significant level), but we further investigated and found there was no indirect v 2 effect (Ogbeibu & Gaskin, 2022;, and based on that, we validate that the GI does not mediate the relationship between TGMO and organization performance. So, our observation comprehends that the functional effect of TGMO has a direct bearing on OP (Papadas et al, 2019) instead of an indirect effect through GI.…”
Section: Moderation Effect Of Svsupporting
confidence: 85%
“…Based on the above discussions, and according to Almotairi (2021)'s report that retailscape consists of three major elements: ambience, exterior and social interaction, the following hypotheses were proposed in relation to tourists' emotional response. Due to the established scales of S-O-R in the retailscape context, the current study examines the direct relationship between exogenous and endogenous variables (Ogbeibu and Gaskin, 2022). Hypotheses were developed in the following.…”
Section: Linking Stimulus-organism-response Model With Retailscape An...mentioning
confidence: 99%
“…One the area where FBR likes to keep focus is proposing new scales especially on the contemporary topics such as Metaverse, Blockchain, Sustainable SCM, Sustainability and Risk Management, Problem Diagnoses, Resilience, etc. For example, FBR has published new scales (Yadav & Poonia, 2021; Yadav & Vihari, 2021) and methodological debates (Ogbeibu & Gaskin, 2022; Saxena et al, 2022) recently. FBR welcomes contributions on across methodologies (empirical, conceptual, qualitative, case based, etc.)…”
Section: Discussionmentioning
confidence: 99%